2009
DOI: 10.1111/j.1755-3768.2008.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of cessation of hyperopia in 123 children with accommodative esotropia treated with glasses for best corrected vision

Abstract: ABSTRACT.Purpose: This study aimed to determine age at successful cessation of hyperopic glasses, the influence of hyperopia on the esotropic angle and age at discontinuation of glasses in accommodative esotropia (AE) patients. Methods: We performed a retrospective study in 123 AE patients who achieved complete emmetropization and maintained orthophoria without hyperopic glasses between March 1999 and February 2005. All patients had been prescribed the weakest possible glasses to provide best corrected vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Several reports have been published regarding safe undercorrection in AET 11–13 22–24. We previously reported a study on patients with AET who achieved emmetropisation and maintained orthotropia without hyperopic glasses, and the subjects had been prescribed the weakest hyperopic glasses to provide best corrected vision and maintain fusion and not full hyperopic correction 13. Consequently, they were able to discontinue wearing hyperopic glasses at an average age of 13.5 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports have been published regarding safe undercorrection in AET 11–13 22–24. We previously reported a study on patients with AET who achieved emmetropisation and maintained orthotropia without hyperopic glasses, and the subjects had been prescribed the weakest hyperopic glasses to provide best corrected vision and maintain fusion and not full hyperopic correction 13. Consequently, they were able to discontinue wearing hyperopic glasses at an average age of 13.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The myopic progression rate per year in AET has been reported to vary widely 4 9–11 13 18 20. Mulvihill et al 18 observed myopic progression rates of 0.005 D/year in the right eye and 0.001 D/year in the left eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 50% of all pediatric esotropias are either entirely or partly accommodative and correction of high hypermetropia with glasses is the primary treatment for accommodative esotropia [13]. Prescription of the full amount of hyperopic correction provides adequate treatment for accommodative esotropia in 75% of cases [14]. Unfortunately these glasses are often poorly accepted by adolescents and young adults for they are cosmetically undesirable, heavy, and esotropia occurs with their removal.…”
Section: Discussionmentioning
confidence: 99%